FAKTOR-FAKTOR YANG MEMENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - admin, Ayu Ambun Sari B11112008 (Jurnal Manajemen Update, 2017)
The purpose of this research is to test both simultaneously and partially to the influence of profitability, asset structure, and company size to the capital structure at food and beverages companies which are listed in Indonesia Stock Exchange on the period of 2010 to 2014. The sampling technique using a purposive sampling and 12 companies have been selected as samples ,while technical analysis using multiple regression analysis. The result of the research shows that this research regressions model has fulfilled the BLUE (Best Linear Unbiased Estimator) requirements that there are no symptoms of heteroscedasticity, multicolinearity, and autocorrelation and the data is normally distributed. According to the research results showed that: (1) The profitability has positive and significant impact on firm’s capital structure. The higher the profitability, the higher the firm’s capital structure. (2) The asset structure has positive and significant impact on firm’s capital structure. The higher the asset structure, the higher the firm’s capital structure. (3) The company size does not affect the firm’s capital structure. Keywords : Profitability, Asset structure, Company size, Capital structure.